WEBSITE DESIGNING MOVIES INFORMATION, BOOKS AND MUSIC INFORMATION USING MACROMEDIA DREAMWEAVER MX 2004 - Hilman Hilman; Ire Puspa W, Ir, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Today's technology is growing rapidly which requires a lot of Man fast-paced information. Especially with the Internet facility which began ogled as a media campaign that quite interesting. To the authors wanted to provide news and information about the film in particular, and little additional information about the book and new album, new music circulated to users who want to know the latest information from the things mentioned above. The site is expected to provide facilities for people who need information about movies, books, and music without having to visit the cinema or bookstore and record store. And this site is created by using the Indonesian language so that the user will be easier to understand.